Editorial Note: Environmental Ethics - A Guide for Disinclined Humanity - Walag, Angelo Mark P. (GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, 2021)
Environmental ethics investigates the relationship between human beings and their surroundings under a more extensive umbrella of environmental philosophy. This field encompasses different disciplines, including those that study human relationships, economics, biology, ecology, and even the arts. In this special issue of GNOSI: An Interdisciplinary Journal of Human Theory and Praxis, environmental ethics has been addressed through various lenses and disciplines. Several papers highlighted the role of religion in shaping and informing environmental ethics, while another article underpinned the importance of literature. Another set of papers also advanced our understanding of the role of virtues apprising environmental philosophy. The rest of the papers examined how we can use environmental ethics in guiding our practices and policies concerning environmental management. All of these perspectives provide us an understanding of the role of environmental ethics in guiding a disinclined and reluctant humanity. The role of religion in informing and guiding environmental ethics has been given attention in three papers in this special issue. One analyzed the Book of Genesis and Isaiah through the socio-ecological lens to explore the human-nature relationship and provide significant clues on how we can address present ecological concerns. Similarly, another paper examined the teachings of Hinduism and Jainism in how it fosters environmental awareness. Both religions stressed the interdependence and interconnectedness of life and environment, which advances our notion of the value of our nature and environment. Another paper also posited that how we take care of the environment can also affect the cultural and religious beliefs of the natives. The authors argued that environmental degradation hindered the practice of some cultural and religious beliefs. When the natives can’t practice their culture or religion, they lose their identity, as these are their identity as an indigen. Aside from the lens of religion, one paper also examines the role of literature and ecocritical writing on advancing campaigns against ecological devastation. These papers highlighted the importance of utilizing different disciplines to draw out essential teachings and lessons to inform and guide humanity. Another set of papers further investigated the value of environmental ethics and nature by identifying essential virtues and environmental virtues. These virtues can help guide and shape how our day-to-day activities by promoting less of the material things and more on the quality of our relationship with the environment and nature. These environmental virtues also provide a framework and a philosophical foundation where we can anchor environmental education. This is possible since environmental virtues provide a rich moral discourse rooted in transformative practice, which our current education emphasizes. Another paper argued the value of nature from a utilitarian perspective and that humans have a duty to take care of the values that nature exhibits, as this is fundamental and indispensable for human survival. Utilitarianism, as a theory, holds that the greatest good is happiness and freedom from pain and suffering. This allows us to see the lens of utilitarianism to be anthropocentric, as the value of nature and the environment depends on how it supports humans. As argued by many environmental ethicists, a steadfast environmental ethic is one that sees all aspects of the environment to be subjects of direct moral concern. As such, environmental ethics should not be only shaped by practical problems alone but also the arguments that appeal to the moral standing of other sentient and non-sentient beings. Although many discussions have centered on the anthropocentric and non-anthropocentric views, our focus must be on the existing and current environmental issues and dilemmas. The opposing views of these theories must not overshadow this environmental agenda. As ethical standings in ethical problems of the environment are placed on the shoulders of individuals, as the only species capable of reason and can decide on significant issues, much should be invested in providing a forum to discuss these theoretical and philosophical underpinnings. The moral standing, as a result, suggests that humans have an ethical obligation toward nature as well as the ability to accomplish the responsibility to take care of it. In this manner, I close this paper by appreciating all the authors from Nigeria, India, the US, South Africa, and France for contributing to this meaningful and relevant discussion on how we can guide humanity to decide morally and virtuously on the environmental problems it presently faces. Dr. Angelo Mark P. Walag, Guest Editor Department of Science Education, University of Science and Technology of Southern Philippines, Cagayan de Oro City, Philippines. Email: walag.angelo@gmail.com